Transcription factor activating enhancer-binding protein 2ε (AP2ε) modulates phenotypic plasticity and progression of malignant melanoma - Stäbler, Sebastian; Rottensteiner-Brandl, Ulrike; El Ahmad, Zubeir; Kappelmann-Fenzl, Melanie; Arkudas, Andreas; Kengelbach-Weigand, Annika; Boßerhoff, Anja Katrin; Schmidt, Sonja (Cell Death & Disease, 2024)
Malignant melanoma, the most aggressive form of skin cancer, is often incurable once metastatic dissemination of cancer cells to distant organs has occurred. We investigated the role of Transcription Factor Activating Enhancer-Binding Protein 2ε (AP2ε) in the progression of metastatic melanoma. Here, we observed that AP2ε is a potent activator of metastasis and newly revealed AP2ε to be an important player in melanoma plasticity. High levels of AP2ε lead to worsened prognosis of melanoma patients. Using a transgenic melanoma mouse model with a specific loss of AP2ε expression, we confirmed the impact of AP2ε to modulate the dynamic switch from a migratory to a proliferative phenotype. AP2ε deficient melanoma cells show a severely reduced migratory potential in vitro and reduced metastatic behavior in vivo. Consistently, we revealed increased activity of AP2ε in quiescent and migratory cells compared to heterogeneously proliferating cells in bioprinted 3D models. In conclusion, these findings disclose a yet-unknown role of AP2ε in maintaining plasticity and migration in malignant melanoma cells.
CRIS-Team Scopus Importer:2024-05-31